Application of HEC-RAS to Estimate the Sediment Transport in Cameron Highlands, Pahang, Malaysia - Mohamad Noor, Dahlia; Abu Talib, Siti Hidayah (Recent Trends in Civil Engineering and Built Environment, 2021)
Sediment deposition which also involved the sediment transport is a key factor in limiting the river development and management. Rivers in Cameron Highlands, Pahang are subjected to rapid deforestation and construction development that bring high impact on the process of sediment transport. This study was carried out to simulate the sediment transport concentration at Sg. Bertam, Cameron Highlands by using one-dimensional (1D) quasi-unsteady flow HEC-RAS. Some information such as hydrological data, geometric data and sediment data are needed to run the simulation. The analysis is done by using Laursen-Copeland method as it performs in the very fine sand and very coarse silt range. The result shows the location of erosion and deposition occurs. The maximum depth of erosion in these reaches is about -0.773 m which happens in RS1537 river stations and the maximum deposition is about 0.794 m in downstream RS636 reach of the river having wide cross section. The maximum sediment concentration along Sg. Bertam is obtained to be 54008.60 mg/L. The main advantage of this study is may assist in achieving sustainability in the implementation of successful strategies for sediment mitigation.